Exosomes-carried microRNA-26b-5p regulates microglia M1 polarization after cerebral ischemia/reperfusion. Issue 9 (2nd May 2020) - Li, Guangying; Xiao, Longhai; Qin, Hao; Zhuang, Qiang; Zhang, Weiwei; Liu, Long; Di, Chao; Zhang, Yabo
ABSTRACT: Exosome and microRNAs (miRs) are implicated in ischemia/reperfusion (I/R) process. In this study, I/R mouse model was established, and exosomes derived from human umbilical cord mesenchymal stem cells (hUCMSCs) were isolated, identified, and injected to I/R mice to observe nerve injury and microglia M1 polarization. The differentially expressed genes in I/R microglia from databases were analyzed, and miRs differentially expressed in exosomes-treated microglia were analyzed by microarray. miR-26b-5p expression in hUCMSCs was intervened. Besides, microglia was extracted and co-cultured with SH-SY5Y or PC12 cells in oxygen-glucose deprivation/reperfusion (OGD/R) models to simulate I/R in vivo . Additionally, Toll-like receptor (TLR) activator GS-9620 was added to microglia. Exosomes alleviated nerve injury and inhibited M1 polarization in microglia. After I/R modeling, CH25H expression in microglia was upregulated but decreased after exosome treatment. miR-26b-5p was upregulated in microglia after exosome treatment and could target CH25H. Reduction in exosomal miR-26b-5p reversed the effects of hUCMSCs-exos on microglia. TLR pathway was activated in microglia after I/R but exosomes prevented its activation. Exosomal miR-26b-5p could repress M1 polarization of microglia by targeting CH25H to inactivate the TLR pathway, so as to relieve nerve injury after cerebral I/R. This investigation may offer new approaches for I/R treatment.